Phasic and 24-h blood pressure control by endothelium-derived relaxing factor in conscious dogs - Persson, Pontus B.; Baumann, J. Ê..; Ehmke, Heimo; Nafz, Benno; Wittmann, Uwe; Kirchheim, Hartmut (American journal of physiology. Heart and circulatory physiology, 1992)
The effects of blocking endothelium-derived relaxing factor (EDRF) on 24-h blood pressure and heart rate (HR) were examined in six conscious freely moving foxhounds. The hypothesis tested was that shear stress-dependent EDRF release acts as a physiological blood pressure buffer. Telemetry recordings were obtained before and after the administration of the false substrate for EDRF synthesis NG-nitro-L-arginine (L-NNA, 16.5 +/- 2 mg/kg body wt iv). In response to L-NNA, mean arterial blood pressure (MAP) increased from 116 +/- 5 to 134 +/- 5 mmHg (P less than 0.01) and HR decreased from 97 +/- 6 to 68 +/- 3 beats/min over the entire 24-h period (P less than 0.01). The overall variability of MAP (as indicated by SD of frequency distribution) increased modestly from 9.5 +/- 0.4 to 11.7 +/- 1.1 mmHg (P less than 0.05). A sequential spectral analysis of blood pressure showed a 2.1-fold increase of power in the frequency range of 0.01-0.5 Hz (P less than 0.05) after L-NNA was given. In conclusion, blockade of EDRF led to a sustained hypertension throughout the whole 24-h recordings. Furthermore, EDRF acted as a physiological blood pressure buffer in the frequency range below 0.5 Hz.